2023
DOI: 10.1111/jcmm.17854
|View full text |Cite
|
Sign up to set email alerts
|

Visfatin aggravates transverse aortic constriction‐induced cardiac remodelling by enhancing macrophage‐mediated oxidative stress in mice

Abstract: Previous studies have reported that visfatin can regulate macrophage polarisation, which has been demonstrated to participate in cardiac remodelling. The aims of this study were to investigate whether visfatin participates in transverse aortic constriction (TAC)‐induced cardiac remodelling by regulating macrophage polarisation. First, TAC surgery and angiotensin II (Ang II) infusion were used to establish a mouse cardiac remodelling model, visfatin expression was measured, and the results showed that TAC surge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
1
0
1
Order By: Relevance
“…Visfatin increased oxidative stress [43], the production of matrix metalloproteinases (such as MMP-9) [44], and collagen deposition. Adiponectin was one of the few anti-in ammatory and protective adipokines.…”
Section: Discussionmentioning
confidence: 99%
“…Visfatin increased oxidative stress [43], the production of matrix metalloproteinases (such as MMP-9) [44], and collagen deposition. Adiponectin was one of the few anti-in ammatory and protective adipokines.…”
Section: Discussionmentioning
confidence: 99%
“…Серцеві ефекти вісфатину. Вісфатин сприяє карді-альному фіброзу, стимулюючи проліферацію кардіальних фібробластів у щурів та активуючи дозрівання проколагену І та ІІІ в цих клітинах [21,42]. Зростання рівня циркуляторного вісфатину корелює зі ступенем нестабільності атеросклеротичних бляшок та оклюзії артерії в зоні некротичного ураження міокарда (infarct-related artery).…”
Section: результати обговоренняunclassified
“…Shen et al . [ 25 ] performed TAC surgery on C57BL/6J mice and found that after 4 weeks, mice showed increased expression of ANP, BNP, and -MHC, increased myocardial cell surface area, fibrosis, increased expression of TGF- 1, increased mRNA expressions of inducible nitric oxide synthase (iNOS), CD36, CD80, and CD86 (M1 markers), and increased mRNA expressions of Arg-1, CD163, and CD206 (M2 markers).…”
Section: Transverse Aortic Constriction Surgerymentioning
confidence: 99%